Analisis Kemampuan Literasi Matematis Siswa dalam Pembelajaran Statistik - Reni Yunita; Sri Hastuti Noer; Chika Rahayu (FKIP Universitas Mataram, 2026)
Mathematical literacy is an individual's capacity to formulate, employ, and interpret mathematics to solve problems in various life contexts. This study aims to analyze students' mathematical literacy skills, specifically in statistics, covering data measures of central tendency and diagram interpretation. The research problem focuses on the extent of students' achievement in meeting literacy indicators and the obstacles encountered in the statistical problem-solving process. The method employed is library research with a qualitative descriptive data analysis technique to examine various relevant literatures. The results indicate that the majority of students' literacy skills fall into the low to moderate category. Although subjects are capable of performing mechanical calculations, significant constraints exist in transforming data into relevant information, misconceptions in visual data, and an inability to communicate solution procedures systematically. Overall, a clear gap was identified between basic procedural mastery and the ability to interpret results in real-world contexts.